2006
DOI: 10.1080/10407780600619535
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer, Phase Change, and Thermocapillary Flow in Films of Molten Metal on a Substrate

Abstract: A mathematical model has been developed for heat transfer and fluid flow in thin films of molten metal during nanosecond pulsed laser irradiation. Heat conduction in the substrate is modeled using the finite-difference approach, while description of heat transfer and viscous flow in the film is based on the assumption of the large ratio of laser beam radius to film thickness and involves numerical solution of a partial differential equation for the thickness. The model includes the highly nonlinear dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…There are situations when the surface tension of an initially flat film is highly non-uniform, e.g., due to rapid localized heating or addition of surfactants. The models of film dynamics under these conditions are discussed by, e.g., Jensen and Grotberg (1992) and Ajaev and Willis (2006) and are beyond the scope of the present review. Our objective is to focus on situations when film breakup is a result of intrinsic instability rather than imposed surface tension gradients.…”
Section: Introductionmentioning
confidence: 99%
“…There are situations when the surface tension of an initially flat film is highly non-uniform, e.g., due to rapid localized heating or addition of surfactants. The models of film dynamics under these conditions are discussed by, e.g., Jensen and Grotberg (1992) and Ajaev and Willis (2006) and are beyond the scope of the present review. Our objective is to focus on situations when film breakup is a result of intrinsic instability rather than imposed surface tension gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the stability and morphological evolution of thin liquid films is vital for a variety of applications such as processing of foam networks (Ashby et al 2000;Banhart 2001), pulsed laser micromachining (Ajaev & Willis 2006) and liquid multilayers (Fisher & Golovin 2005). For example, in a foam, there are sections of crowded gas bubbles separated by uniform, thin, liquid lamella.…”
Section: Introductionmentioning
confidence: 99%
“…Models for this configuration have also incorporated evaporative mass transfer effects due to the high-energy flux. The thin film approximation is still applicable, and a non-linear equation for the film thickness has been derived [13]. Experimental work has shown that the interface can undergo instabilities that lead to droplet and ring formations that may be exploited for circuit fabrication [14].…”
Section: Introductionmentioning
confidence: 99%